Self-Efficacy in Salt Consumption Among Patients Undergoing Hemodialysis - Desy Listyaningrum; Melyza Perdana; Anita Kustanti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
Salt consumption restriction has many advantages in patients on hemodialysis (HD), but it is also very challenging for them. Self-efficacy is a crucial aspect of successful disease management. Factors related to self-efficacy have been evaluated in many countries. However, the different demographic characteristics in Indonesia may show different significant results. Understanding this problem may contribute to the development of nursing interventions and the patients’ self-management ability while undergoing HD. Hence, the present study aimed to determine the factors associated with self-efficacy for restricting salt consumption among HD patients. Altogether, 98 HD patients participated in this cross-sectional study. The Self-efficacy for Restricting Dietary Sodium in Hemodialysis Scale questionnaire was completed to assess the patients’ self-efficacy. Linear regression was performed to evaluate the relationship between self-efficacy and patient characteristics. The participants’ mean age was 50.11 ± 1.29 years and the mean self-efficacy score was 73.56 ± 14.85. Mostly, participants were male (60.2%), married (82.7%), and had hypertension (85.7%). Age (p = 0.000; r = 0.384), HD duration (p = 0.004; r = −0.287), and interdialytic weight gain (IDWG) (p = 0.008; r = −0.267) significantly correlated with self-efficacy for restricting salt consumption. These three variables determined 21% of the variance of self-efficacy among HD patients. The present study provides primary evidence that age, HD duration, and IDWG are associated with self-efficacy for restricting salt consumption among HD patients. Thus, nurses could develop innovative interventions to enhance the self-efficacy among patients with younger age, longer HD duration, and more IDWG. Keywords: hemodialysis, salt consumption, self-efficacy Abstrak Efikasi Diri dalam Konsumsi Garam di Kalangan Pasien yang Menjalani Hemodialisis. Pembatasan asupan garam pasien hemodialisis (HD) bermanfaat bagi kondisi kesehatan sekaligus menjadi tantangan tersendiri bagi pasien. Efikasi diri merupakan aspek mendasar dalam keberhasilan manajemen penyakit. Faktor yang berhubungan dengan efikasi diri sudah diteliti di negara-negara lain, akan tetapi, perbedaan karakteristik demografi di Indonesia dapat memperlihatkan perbedaan hasil. Pemahaman terkait masalah ini berkontribusi pada peningkatan intervensi keperawatan dan manajemen diri pasien. Oleh karena itu, tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan efikasi diri dalam membatasi asupan garam pada pasien hemodialisis. Penelitian ini menggunakan desain cross-sectional dengan melibatkan sebanyak 98 pasien. Kuesioner The self-efficacy for Restricting Dietary Sodium in Hemodialysis Scale digunakan untuk mengukur efikasi diri pasien. Regresi linear dilakukan untuk melihat hubungan antara efikasi diri dengan data demografi. Rata-rata usia partisipan adalah 50,11 ± 1,29 tahun dengan rata-rata skor efikasi diri pasien adalah 73,56 ± 14,85. Sebagian besar partisipan adalah laki-laki (60,2%), sudah menikah (82,7%), dan memiliki hipertensi (85,7%). Ditemukan bahwa usia (p = 0,000; r = 0,384), durasi hemodialisis (p = 0,004; r = −0,287), dan IDWG (p = 0,008; r = −0,267) berhubungan signifikan dengan efikasi diri dalam membatasi asupan garam. Ketiga variabel tersebut berkontribusi sebesar 21% terhadap variansi efikasi diri pasien hemodialisis. Penelitian ini membuktikan bahwa usia, durasi hemodialisis, dan IDWG berhubungan dengan efikasi diri pembatasan asupan garam pasien hemodialisis. Oleh karena itu, perawat dapat mengembangkan intervensi peningkatan efikasi diri pada pasien dengan usia muda, pasien yang telah lama menjalani HD, dan pasien dengan IDWG lebih. Kata Kunci: asupan garam, efikasi diri, hemodialisis